2022
DOI: 10.15639/teflinjournal.v33i1/1-26
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions and Practices of Critical Thinking Instruction in Indonesian Senior High Schools: A Case Study

Abstract: This study investigated how Indonesian teachers perceived and incorporated critical thinking concepts in English language classrooms. A case-study approach was set out to investigate teacher’s perceptions and practices of critical thinking in teaching English language to twelfth-grade students in Jambi Province, Indonesia. Semi-structured interviews, classroom observation, and stimulated-recall interviews were employed to collect data from six teachers in six different senior high schools. The semi-structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…However, the results of the research investigating the correlation between two predictor variables simultaneously, namely critical thinking skills and science process skills, towards learning results have not been revealed. The correlational study between critical thinking skills and learning results found a significant correlation between critical thinking skills and learning results based on levels of education [1], [2]. Another researches also reported a significant correlation between critical thinking skills and learning results based on different learning models [3]- [5].…”
Section: Introductionmentioning
confidence: 86%
“…However, the results of the research investigating the correlation between two predictor variables simultaneously, namely critical thinking skills and science process skills, towards learning results have not been revealed. The correlational study between critical thinking skills and learning results found a significant correlation between critical thinking skills and learning results based on levels of education [1], [2]. Another researches also reported a significant correlation between critical thinking skills and learning results based on different learning models [3]- [5].…”
Section: Introductionmentioning
confidence: 86%
“…Teachers are required to be able to use technology and be smart in knowing the learning situation [22]. The application of learning with a learning model that can engage students actively in the learning process is one of many factors that must be taken into account in the learning process to increase the quality and quality of learning outcomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…A good education is one that is capable of producing output or achievement and quality and has abilities that can benefit others (Nurhasni et al, 2020). This ability will not be separated from the implementation of the ongoing learning process (Anggraeny & Khongput, 2022).…”
Section: Introductionmentioning
confidence: 99%